2020
DOI: 10.1007/s13167-020-00216-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cohort study data affect external validation of artificial intelligence models for predictive diagnostics of dementia - lessons for translation into clinical practice

Abstract: Artificial intelligence (AI) approaches pose a great opportunity for individualized, pre-symptomatic disease diagnosis which plays a key role in the context of personalized, predictive, and finally preventive medicine (PPPM). However, to translate PPPM into clinical practice, it is of utmost importance that AI-based models are carefully validated. The validation process comprises several steps, one of which is testing the model on patient-level data from an independent clinical cohort study. However, recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
(46 reference statements)
0
33
0
Order By: Relevance
“…To validate discoveries made in ADNI on other datasets, a high overlap in measured variables is a prerequisite. Previously, we could demonstrate that despite evident differences to ADNI, ANMerge is a viable validation dataset [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To validate discoveries made in ADNI on other datasets, a high overlap in measured variables is a prerequisite. Previously, we could demonstrate that despite evident differences to ADNI, ANMerge is a viable validation dataset [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To validate discoveries made in ADNI on other datasets, a high overlap in measured variables is a prerequisite. Previously, we could demonstrate that despite evident differences to ADNI, ANMerge is a viable validation dataset (Birkenbihl et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To validate discoveries made in ADNI on other datasets, a high overlap in measured variables is a prerequisite. Previously, we could demonstrate that despite evident differences to ADNI, ANMerge is a viable validation dataset(Birkenbihl et al, 2020).Recently, more studies such as PREVENT-AD (Tremblay-Mercier et al, 2014) and EPAD (Solomon et al, 2018) joined the ranks of ADNI, DIAN (Morris et al, 2012) and others by making their data accessible to third party researchers. The currently running Deep Frequent Phenotype Study (Lawson et al, 2017) already emphasized that collected data will be published.…”
mentioning
confidence: 92%
“…A summary [14] of the properties of AD cohorts shows that AD cohorts differ with regards to study location, study size, recruitment criteria, diagnosis method and biomarkers. A comparison [15] of two AD cohorts, the Alzheimer's Disease Neuroimaging Initiative (ADNI) [16] and AddNeuroMed [17] found major demographical differences between the AD cohorts using a statistical matching procedure. It was found that the demographics of the AddNeuroMed data set were less diverse than the subjects of the ADNI data set.…”
Section: External Validationmentioning
confidence: 99%